PENGARUH PEMBERIAN PUPUK NPK SLOW RELEASE LAPIS HUMAT TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT (Lycopersicum esculentum Mill.) - Dewi Novita Rahma; Widiwurjani Widiwurjani; Sukendah Sukendah (Jurnal Ilmiah Hijau Cendekia, 2022)
Tomato (Lycopersicum esculentum Mill.) is a vegetable crop that is an alternative source of income for farmers. Fertilization efficiency with the addition of humic acid can reduce the use of anorganic fertilizers. Organic matter from humic acid can improve physical, chemical, biological properties and improve soil fertility status which can absorb and provide nutrients for plants. The humic layer NPK will be slow release, nutrients are released according to plant needs. The study aimed to determine the dose of humic layered slow release NPK fertilizer on the growth and yield of tomato plants was carried out in Klagen Gambiran Village, Maospati District, Magetan Regency from February to May 2020. The materials used were servo f1 varieties, NPK fertilizer (16:16:16) and NPK slow release humic layer. The study was arranged using a non-factorial Randomized Block Design (RAK) with 6 levels of treatment, 4 replications, namely: dose P0 = 300 kg/ha without humic (control), P1 = 100 kg/ha, P2 = 150 kg/ha, P3 = 200 kg/ha, P4 = 250kg/ha, and P5 = 300 kg/ha. The results showed that the application of slow release humic layer NPK fertilizer of 300 kg/ha (P5) had a very significant effect on plant height, number of leaves, number of fruit per plant per harvest, total fruit number of plants, fruit weight per plant per harvest and total fruit weight plant.